Investigation of hydro-mechanical processes in fluid-saturated fractured rock based on numerical model generation. Issue 1 (August 2021) - Pollmann, N; Gallas, J; Brandenburg, M Ch; Witte, L; Backers, T
Abstract: To realistically simulate fluid flow in fractured rock mass, a scheme to represent the discrete fracture networks (DFN) in the numerical model is of utmost importance. In this paper we discuss a workflow to implement a field-measurement based DFN into an FEM code (COMSOL Multiphysics) by means of a MATLAB routine. This workflow is involved in the ZoKrateS project which aims at showing the feasibility to enhanced fractured carbonate Rock Mass by proppant placement for geothermal application. The model generation is based on analytical geometry including the equations for dip, azimuth and spacing of lines. The spacing between the discontinuities and the characteristic fracture length and aperture as well as orientation serve as input parameters for the model. It is possible to generate periodic models to be able to include periodic boundary conditions in simulations. In 2D the fractures are modeled as poroelastic ellipses in a poroelastic square-matrix. We investigate hydro-mechanically triggered fluid transport in stationary fractures that are mechanically and hydraulically active. An extension to 3D fracture networks requires an algorithm based on analytical geometry including the equations for azimuth, dip and spacing of planes. To decrease the numerical costs of the 3D simulation a diffuse interface approach is strived for, including a modified model generation. With the numerical model generator (NUMOG) a workflow is developed which allows numerical investigations of (thermo-) hydro-mechanically triggered fluid transport in a geothermal reservoir.